Na sombra do imbuzeiro armamos nossas redes: construção social da cultura organizacional da Associação de Agricultores Alternativos em Alagoas - Silva, José Ribeiro da (2023)
Although studies on organizational culture have increased significantly from the 1980s onwards, few have been directed to the analysis of representative social organizations, especially those made up of family farmers. The cultural dimension in these organizations is mostly neglected, not knowing their constructive process, as well as their diversity in terms of expressions, symbolism and meanings, aspects that can influence the adaptive strategies of this type of organization to constant changes in context , which can determine their survival. In this sense, this thesis aimed to analyze the construction process and current expressions of the organizational culture of an association of family farmers that, based on alternative processes of ATER, has been throughout its history seeking strategies for the socioeconomic inclusion of these farmers through agriculture. of ecological base, solidary economic relations and contextualized rural education, in an environment in constant transformations. The study was based on the experience of the Associação de Agricultores Alternativos (AAGRA), an organization founded in 1989 by farmers from the Alagoan municipalities of Palmeira dos Índios and Igaci, animated by technicians linked to popular education movements that sought to break with the paradigm of an environment where droughts were the basis of dominant narratives to justify poverty, hunger and the pretentious charity of local politicians. For this, I adopted ethnography as a methodological direction, instrumentalized by participant observations, document analysis, interviews with a semi-structured script and conversation circles. The analyzes took into account the strategy for elaborating the organizational biography proposed by Fleury; the levels of organizational culture elaborated by Schein; and, the metaphor of organisms as proposed by Morgan. The description and analysis of the organizational biography considered the moment of its foundation in 1989 as a starting point and the year 2022 as an arrival point. During this period, it was identified that the organization went through at least four cycles that challenged its survival . These moments were influenced by the dynamics of the organizational and institutional environment, providing internal changes linked to behaviors, norms and administrative processes. In addition, the definition of strategies for overcoming environmental adversities, enabled the development of new projects which expanded its area of action to the state level, starting to involve other cultural groups. What results from this constructive process is a diverse, resilient and welcoming organizational culture. Diverse for working with communities from different cultural backgrounds and for creating spaces for gender and generational representations. Facing environmental adversities makes it resilient without compromising its management processes based on social participation and transparency in the use of resources. AAGRA, throughout its historical process, has welcomed and still welcomes groups and individuals excluded from public policies, seeking to insert them into socioeconomic dynamics, even if, for that, it has to make its membership and permanence criteria temporarily more flexible.